Compare of post traumatic stress disorder between parents of term and pre term infants - Ghorbani, Maryam; Dolatian, Mahrokh; Shams, Jamal; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2015)
Background and aim: Post traumatic stress disorder is a severe disorder that happens by encountering with a distressing psychological experience, and leads to revealing disease symptoms. About 1/5 to 6 percent of women in the world, have post traumatic stress disorder following delivery. Pregnancy is as a risk factor of this disease. also it has been detected that fathers of preterm babies experience more stress than fathers of term babies. Materials and methods: this study was a descriptive-comparetive study. The sample size was 82 parents in two group of term and preterm babies. The tools of this study was demographic and PSS-I questionnaire that parents filled them 2month after their baby birth. Data was analyzed with X2 , exact fisher test, Mann-whitney and independent t test with SPSS18. Findings: post traumatic stress was significantly more in mothers of preterm babies (p=0/03). But there were no significant difference between fathers in two group (p=1). Conclusion: mothers of preterm babies are at more risk than fathers for psychological problems and this finding shows the need for more intervention to help them to cope with problem of having preterm babies. Keywords: post traumatic stress disorder, prematurity, parents